Fiscal Policies and Economic Growth of Kosovo - Hamza Bedri; Milo Petraq (Economics and Business)
Fiscal policy is of great importance for Kosovo’s economic development. This study aims at analysing the tax system in Kosovo in the theoretical and analytical terms. The data used are secondary taken from state budget and include tax revenues as well as budget expenditures between 2006 and 2018. Observance of tax laws is an essential civic responsibility. In a modern country, which Kosovo aims to be, citizens are required to pay taxes and other obligations which fund government programs, the provision of public services and high standards of education, welfare, health, social support, protection, law enforcement and general infrastructure. All of these can be secured and made possible only in the proper collection of taxes. The study concludes that tax policy plays a very important role in the collection of taxes and duties as well as in the fair distribution of the budget.